Workerâ€™s Rights According To Islamic Law Perspective (The Principle of Mudharabah) That Can Be Applied In Trade and Investment Agreements (Lex Jurnalica, 2006)
Many experiences have shown that the working conditions can be related to the contract between the laborers and the company or the employer. Sometimes the collective bargaining power of the workers to the employers can not bring the workers much hope for their betterment in the future because of many restrictions in the government rules towards labor. This kind of contract brings an opposition status between the employer and the laborers. The opposition between the workerâ€™s to the company. Linguistically, the word Mudharabah is used to signify an idea of â€œgiving out a part of capital to somebody to trade in, provided that the profit is shared between them in which an apportioned share is allocated to the activity of trader in doing the businessâ€. In the fields of labor law, Mudharabah principle can also be applied in the contract between the capital owner and the laborers. The principle of the Mudharabah comes from the point of view thatÂ  all human beings are equal. Equal in sense that he or she has dignity and that all of them are workers, since no bodyis exempted or to live without some kind of exertion of effort, except for disabilities. There is no concept in Islamic that one class or one group in society is above or superior to the other. In an ideal Islamic society that Islam teaches, there is no subdivisions of classes that these are the group or the class of entrepreneur or managers and these are workers.Keywords: Workers Rights, Islamic Law, Trade and InvestmentÂ Â  Agreement